Assessment of municipal solid waste composition in Malaysia: management, practice, and challenges. - Badgie, Dawda; Abu Samah, Mohd Armi; Abd Manaf, Latifah; Muda, Azizi (2012)
Malaysia is faced with daunting challenges related to solid waste management. Due to an increase in population, economic growth, inadequate enforcement of waste legislation, infrastructure, and public attitude among others, solid waste management is considered a crucial issue in Malaysia, particularly in urban settings. This paper gives an overview of solid waste management in Malaysian with the aim of presenting the state of waste generation, composition, management practices, and problems with regards to environmental, economic, and other ramifications from previous records. In general, the total waste generated in Malaysia is estimated to be 7 million tons in 2000, with an annual increase of 3%. This is due to many factors such as urban migration, affluence, and rapid development. This circumstance requires greater focus to be in placed on managing solid waste and mitigating the negative public and environmental effects. Presently, management of solid waste is carried out by the Ministry of Housing and local government, with the support of the private sector. This new holistic approach initiated addressing the solid waste issue, taking into account public health and environmental concerns with an emphasis on reduction, reuse, and recycling before reaching final stage – disposal at landfill, and this to certain extent has a greater potential in addressing SWM problems in Malaysia.